Diversity, relative abundance, and functional genes of intestinal Microbiota of Tiger Grouper (Epinephelus fuscoguttatus) and Asian Seabass (Lates calcarifer) reared in a semi-closed hatchery in dry and wet seasons - Sutra, Jumria; Saadu, Hamidu; Mohd. Hashim, Amalia; Saad, Mohd Zamri; Md Yasin, Ina Salwany; Amal, Mohammad Noor Azmai (Universiti Putra Malaysia Press, 2021)
Grouper and Asian seabass are among the economically important cultured marine fish in Malaysia. However, fry productions in large scale tend to introduce stress that changes the fish microbiota and increases susceptibility to diseases. Currently, high through put sequencing is used to study fish microbiota and their respective gene functions. In this study, the diversity, abundance and functional genes of intestinal microbiota of tiger grouper and Asian seabass that were reared in a semi-closed hatchery during dry and wet seasons. Intestinal samples were collected from tiger grouper and Asian seabass of different sizes before proceeded to DNA extraction. The extracted DNA were then subjected to 16S rRNA gene amplicon sequencing using the Illumina Miseq platform targeting V3 and V4 regions for determination of the bacterial diversity, abundance and functional genes in both seasons were investigated. The results revealed that intestinal microbiota of Asian seabass were dominated by the phylum Proteobacteria and order Vibrionales in both seasons. Meanwhile, intestinal microbiome of tiger groupers were shifted from domination of phylum Firmicutes and order Clostridiales in dry season to Proteobacteria and order Lactobacillales in wet season. PICRUSt analysis revealed that the functional genes that were dominantly present were the genes encoded for metabolism, genetic information processing, environmental information processing, cellular process and human diseases. Remarkably, SIMPER analysis showed several potential metagenomics biomarker genes in dry and wet seasons. This study revealed the importance of utilizing amplicon metagenomics approaches in microbiome studies for better identification of the microbial profiling in aquaculture systems.